The Role of Erector Spinae Plane Block in Percutaneous Nephrolithotomy Pain Management - Septian, Muhammad Raditia; Giani, Maia Thalia (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2024)
Background: The erector spine plane block (ESPB) is a novel peripheral nerve block approach between the erector spinal muscle and the thoracic transverse processes. It blocks multiple dermatomal sensory nerves in the thoracic and abdominal walls. ESPB is widely used in thoracoabdominal surgery, including percutaneous nephrolithotomy (PCNL). This review aims to assess the role of ESPB in PCNL.Methods: A Literature search was performed systematically with the medical terms “erector spinae plane block” and “nephrolithotomy” in PubMed, ScienceDirect, Cochrane Library, and Google Scholar until April 30, 2022. Two independent reviewers screened the articles for inclusion based on relevancy to the subject and outcomes. Data extraction was conducted for the included studies. The result from these studies demonstrates the efficacy of ESPB in PCNL.Results: A total of 267 literatures according to the search strategy. Nineteen studies were included in this review after excluding the duplicated, non-English, and irrelevant studies based on the title or abstract. From the full article review, 11 studies were with 644 patients. ESPB group had a significantly superior outcome of decreasing pain score compared to the conventional analgesia, tramadol intravenously, and placebo. ESPB had no significantdifferences with intrathecal morphine on the pain scale and first analgesic request. The timing of the first rescue analgesia in the ESPB group was longer and the procedure also reduced opioid requirement in PCNL patients. Conclusion: ESPB is a potentially effective technique to provide post-PCNL analgesia. ESPB provides pain relief after surgery, prolongs time to take additional analgesic drugs including postoperative opioid consumption.